PERAN CITRA MEREK DALAM MEMEDIASI PENGARUH KUALITAS PRODUK TERHADAP NIAT BELI - Suandayana, Ida Bagus Putu; Setiawan, Putu Yudi (E-Jurnal Manajemen, 2019)
The purpose of this study is to determine the effect of product quality on brand image on Apple macbook latop, to know the effect of product quality and brand image on purchase intention on Apple Macbook laptop product, and to know the role of brand image in mediating the effect of product quality on buying intention. The population of this study is all respondents who are domiciled in Denpasar City who have the intention to buy Apple Macbook laptops. A sample of 112 respondents from all parts of Denpasar City. The data was analyzed using the PLS Method (Partial Least Square). The results show that the effect of product quality and brand image partially have a positive and significant effect on purchase intention on Apple Macbook laptops, and product quality partially positively and significantly influence to the brand image on Apple Macbook laptops. The results also show that brand image is able to mediate the influence of product quality on purchase intention. Keywords: product quality, brand image, purchase intention